Can Africa Replicate Asia's Green Revolution in Rice? - Larson, Donald F.; Otsuka, Keijiro; Kajisa, Kei; Estudillo, Jonna; Diagne, Aliou (2012)
Asia's green revolution in rice was transformational and improved the lives of millions of poor households. Rice has become an increasingly important part of African diets and imports of rice have grown. Agronomists point out that large areas in Africa are well suited for rice and are encouraged by the field tests of new rice varieties. So is Africa poised for its own green revolution in rice? This study reviews the recent literature on rice technologies and their impact on productivity, incomes, and poverty, and compares current conditions in Africa with the conditions that prevailed in Asia as its rice revolution got under way. An important conclusion is that, to a degree, a rice revolution has already begun in Africa. Moreover, many of the same practices that have proved successful in Asia and in Africa can be applied where yields are currently low. At the same time, for many reasons, Africa's rice revolution has been, and will continue to be, characterized by a mosaic of successes, situated where the conditions are right for new technologies to take hold. This can have profound effects in some places. But because diets, markets, and geography are heterogeneous in Africa, the successful transformation of the Africa's rice sector must be matched by productivity gains in other crops to fully launch Africa's Green Revolution.